Structural Dependence of Sulfated Polysaccharide for Diabetes Management: Fucoidan From Undaria pinnatifida Inhibiting α-Glucosidase More Strongly Than α-Amylase and Amyloglucosidase - Koh, Hui Si Audrey; Lu, Jun; Zhou, Weibiao (Frontiers in Pharmacology, 2020)
Fucoidan refers to a group of sulfated polysaccharide that is commonly obtained from various species of brown seaweed. Fucoidan has gained increased popularity among researchers in the recent years due to its numerous biological activities, including its inhibitory effects against starch hydrolyzing enzymes such as α-amylase and α-glucosidase. This highlights the potential of fucoidan as an antidiabetic agent in the management and prevention of diabetes mellitus. In this study, the inhibitory effects of fucoidan isolated from the New Zeaweed Undaria pinnatifida seaweed species against three starch hydrolyzing enzymes – α-amylase, α-glucosidase and amyloglucosidase was investigated. It was demonstrated that while the fucoidan exhibited significant inhibitory effects against all the three starch hydrolases, it is an uncompetitive inhibitor of α-amylase and amyloglucosidase, and is a competitive inhibitor of α-glucosidase. Moreover, it exhibited significantly stronger inhibitory effects against α-glucosidase than α-amylase, thus having the desirable characteristics as an antidiabetic agent.